Phylogenetic relationship of Kappaphycus and Eucheuma in Indonesia / Eka Sunarwidhi Prasedya - Eka Sunarwidhi , Prasedya (2013)
Kappaphycus and Eucheuma are highly valued for the carrageenan hydrocolloid they produce. The production of these carrageenophytes is generally on the uptrend throughout the globe, with the supplies originating mainly from the Southeast Asian countries such as Indonesia, the Philippines and, Malaysia and etc. Indonesia is currently the largest producer of Kappaphycus and Eucheuma in the world, generating massive incomes from the carrageenan marketed. Despite the massive carrageenan yields, the technologies involved in farming are conventional and taxing, with many still collecting Kappaphycus and Eucheuma from wild populations. However, with recent fundings and support from the local government, the seaweed industry in Indonesia stands a chance in really striving to become an advanced, high income and efficient entity. One of the aims for the improvement of the industry involves taxonomic studies on the morphologically plastic Kappaphycus and Eucheuma from Indonesia, to reduce misidentification and misplantation by farmers, thereby also reducing losses in overall carrageenan yields. Earlier studies have shown the effectiveness of genetic markers in elucidating the phylogeny of Kappaphycus and Eucheuma. This study employs similar methodologies, with a main objective which is to phylogenetically reconstruct and elucidate the relatedness and ancestry of Kappaphycus and Eucheuma in Indonesia, as compared to those from elsewhere. The study also attempts to supplement morphological observations of these carrageenophytes in Indonesia with molecular data, which hopefully will help with the pre-existing taxonomic confusions, particular those associated with local varieties. gene had also suggested the potential use of these genetic markers as DNA barcodes for Kappaphycus and Eucheuma in the future. Considering the relatively limited gene pool associated with commercial cultivars of K. alvarezii, K. striatum and E. denticulatum, further studies should emphasize on the collection of wild Kappaphycus and Eucheuma specimens revolving around the numerous Indonesian islands to better represent the distribution as well as species diversity of these economically important red algae. This is especially true considering the richness in biodiversity around the Coral Triangle.